Trade facilitation and better connectivity for an inclusive Asia and Pacific. (Asian Development Bank, 2017)
Trade facilitation increases trade flows, lowers trade cost, and ultimately contributes to sustainable and inclusive growth. This publication, jointly prepared by the Asian Development Bank and the United Nations Economic and Social Commission for Asia and the Pacific, reviews the state of play of trade facilitation and paperless trade in Asia and the Pacific. It investigates the evolution of trade costs in the region, examines trade facilitation and paperless trade implementation, and highlights the key initiatives and efforts in Central Asia, the Greater Mekong Subregion, South Asia, and the Pacific. It includes impact assessments of trade facilitation implementation and corridor performance on reducing trade costs and increasing trade.